1987
DOI: 10.2307/3503918
|View full text |Cite
|
Sign up to set email alerts
|

Martes americana

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 37 publications
(75 reference statements)
0
41
0
Order By: Relevance
“…Members of the genus Martes are small-bodied (mean total skull length of 75 mm according to Elbroch, 2006) mesocarnivorous to hypercarnivorous mustelids (Ben-David et al, 1997;Hickey et al, 1999;Cumberland et al, 2001) that, like felids, have been reported to kill their prey via a precise bite to the neck (Clark et al, 1987). Much of the caloric content of the diet in some members of this genus, such as M. americana, is composed of larger prey items (Cumberland et al, 2001), such as grouse (Bonasa umbellus and Canachites canadensis) and snowshoe hares (Lepus americanus).…”
Section: Paleobiology Of Uf 27881mentioning
confidence: 99%
“…Members of the genus Martes are small-bodied (mean total skull length of 75 mm according to Elbroch, 2006) mesocarnivorous to hypercarnivorous mustelids (Ben-David et al, 1997;Hickey et al, 1999;Cumberland et al, 2001) that, like felids, have been reported to kill their prey via a precise bite to the neck (Clark et al, 1987). Much of the caloric content of the diet in some members of this genus, such as M. americana, is composed of larger prey items (Cumberland et al, 2001), such as grouse (Bonasa umbellus and Canachites canadensis) and snowshoe hares (Lepus americanus).…”
Section: Paleobiology Of Uf 27881mentioning
confidence: 99%
“…Food habits of primary mustelid hosts may be characterized as opportunistic, although arvicoline rodents are considered to be dominant through the annual cycle based primarily on scat analysis (e.g., Strickland et al, 1990). Insectivores, including species of Sorex, have been identified as prey for martens in Alaska but appear to be a minor component of the diet, most often represented during the winter (Buskirk and MacDonald, 1984;Clark et al, 1987). Our studies may establish the basis for recognizing shrews as important paratenic hosts involved in transmission of S. baturini.…”
Section: Discussionmentioning
confidence: 97%
“…Body weights were taken from BinindaEmonds (1998) and Nowak (1997), complemented with data from the series ''Mammalian Species'' (Estes 1980;Powell 1981;Clark et al 1987;Youngman 1990;Kinlaw 1995;Pasitstschniak-Arts and Larivière 1995;Sheffield and Thomas 1997;Larivière and Walton 1998;Larivière 1999;2001a;2001b;Verts et al 2001). Data on the length of the breeding season were taken from Mead (1989).…”
Section: Methodsmentioning
confidence: 99%